2019
DOI: 10.1002/aenm.201902125
|View full text |Cite
|
Sign up to set email alerts
|

An Air‐Stable and Dendrite‐Free Li Anode for Highly Stable All‐Solid‐State Sulfide‐Based Li Batteries

Abstract: Li metal is a promising anode material for all‐solid‐state batteries, owing to its high specific capacity and low electrochemical potential. However, direct contact of Li metal with most solid‐state electrolytes induces severe side reactions that can lead to dendrite formation and short circuits. Moreover, Li metal is unstable when exposed to air, leading to stringent processing requirements. Herein, it is reported that the Li3PS4/Li interface in all‐solid‐state batteries can be stabilized by an air‐stable Lix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 40 publications
8
86
0
Order By: Relevance
“…Expect from the above methods, covering the surface of the Li foil with a lithiophilic layer is another effective way to protect the Li metal anode. Till now, it has been reported that ZnO/carbon nanotube (CNT), Au, S, P, Sn, and Si have been reported to inhibit Li dendrites (Lin et al, 2018;Zhang X. Q. et al, 2018;Guo et al, 2019;Liang et al, 2019;Xia et al, 2019). Chen et al used sulfur vapor to react with Li then transform into Li 2 S on the Li surface .…”
Section: Introductionmentioning
confidence: 99%
“…Expect from the above methods, covering the surface of the Li foil with a lithiophilic layer is another effective way to protect the Li metal anode. Till now, it has been reported that ZnO/carbon nanotube (CNT), Au, S, P, Sn, and Si have been reported to inhibit Li dendrites (Lin et al, 2018;Zhang X. Q. et al, 2018;Guo et al, 2019;Liang et al, 2019;Xia et al, 2019). Chen et al used sulfur vapor to react with Li then transform into Li 2 S on the Li surface .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the electrochemical performance of the pristine Li after air exposure decreases apparently compared to the fresh Li, indicating the dual‐layered film effectively prevents Li from air corrosion, offering an alternative to assemble LMBs without inert atmosphere. Moreover, by a simple two‐step solution‐based reaction among Li, Li 2 S 8 , and SiCl 4 , an air‐stable Li anode with an in situ formed Li x SiS y coating layer also can be achieved (Li‐Li x SiS y , Figure 7(B‐i)) 95 . According to thermal gravimetric analysis (Figure 7(B‐ii)), there is almost no weight change of Li‐Li x SiS y foil during 24 h exposure to air.…”
Section: Air Instability Of Lithium Metal Anode: Problems Solutionsmentioning
confidence: 99%
“…Reproduced with permission: Copyright 2019, Wiley‐CVH 94 . (B‐i) Schematic of the fabrication process of Li‐Li x SiS y ; (B‐ii) thermal gravimetric analysis of Li‐Li x SiS y and bare Li in air over time; (B‐iii) time‐of‐flight secondary ion mass spectrometry (TOF‐SIMs) secondary ion images of Li‐Li x SiS y before (top) and after (bottom) Cs + conductive sputtering for 300 s; and (B‐iv) TOF‐SIMS secondary ion images of Li‐Li x SiS y before (top) and after (bottom) Cs + conductive sputtering for 300 s after anode exposing to ambient air for 5 h. Reproduced with permission: Copyright 2019, Wiley‐VCH 95 …”
Section: Air Instability Of Lithium Metal Anode: Problems Solutionsmentioning
confidence: 99%
“…As for the Li/wet separator/Li cell, the polarization voltage increases significantly (bigger than 110 mV) compared to that of the Li/GPE/Li cell at the beginning (the insets in Figure 4 b). At the 91 st cycle, the polarization voltage decreases suddenly, illustrating the occurrence of the short circus in the Li/wet separator/Li because of the continual growth of metallic dendrites [ 34 ]. Shown as the dissemble Li/wet separator/Li cell ( Figure 4 d), the inhomogeneous SEM layer and lots of lithium dendrites rooting from the nonuniform ion plating/stripping are presented clearly.…”
Section: Resultsmentioning
confidence: 99%